USING EDUCATIONAL TECHNOLOGIES FOR EFFECTIVE DELIVERY OF DISTANCE EDUCATION - Bahronqulova , Malika Akmal qizi; Murodullayeva , Sarvinoz Yorqin qizi; Burkhanova, Mamura Gulyamovna (Innovative Development in Educational Activities, 2022)
In this article the information is given about the technologies based on education in distance learning. The article also clarifies how to use these technologies during e-learning and structures of utilizing a new platform called “ Nearpod”.